A Política na Pedra - Samara, Maria Alice (Trabalhos de Antropologia e Etnologia, 2020)
This article analyses a central space in Lisbon, based on the idea that politics and worldviews are also inscribed in stone, in the monuments and in the materiality of the city. The territory between Praça do Marquês de Pombal and Rossio is analysed taking into account both what has been inscribed, as well as the manifestations that question and subvert the original meanings, recognizing this space as a territory for fighting for memory and history.